Nasopharyngeal and Oropharyngeal Colonization by Staphylococcus aureus and Streptococcus pneumoniae and Prognostic Markers in Children with Sickle Cell Disease from the Northeast of Brazil - Rocha, Larissa C.; Carvalho, Magda O. S.; Nascimento, Valma M. L.; dos Santos, Milena S.; Barros, Tânia F.; Adorno, Elisângela V.; Reis, Joice N.; da Guarda, Caroline C.; Santiago, Rayra P.; Gonçalves, Marilda de Souza (Frontiers in Microbiology, 2017)
We investigated the nasopharynx and oropharynx microbiota in sickle cell disease (SCD) to identify the microorganisms, antibiotic sensitivity, prevalent serotypes, and association of with laboratorial markers. Oropharynx/nasopharynx secretions were investigated in 143 SCD children aging 6 months to 17 years. Pathogens were isolated using standard procedures, and laboratorial markers were performed by automated methods. Staphylococcus aureus (S. aureus) was isolated from nasopharynx and oropharynx of 64 and of 17 SCD children respectively. Streptococcus pneumoniae (S. pneumoniae) was isolated from the nasopharynx and oropharynx of eight SCD patients. Serotypes of S. pneumoniae were 19F, 23F, and 14. All isolates were susceptible to penicillin, and patients whose nasopharynx and oropharynx were colonised by S. pneumoniae had high concentrations of aspartate transaminase, alanine transaminase, and ferritin. S. pneumoniae isolated were not penicillin-resistant serotypes suggesting that the use of penicillin for prophylaxis and/or treatment of infections is safe. Our finding of colonisation and laboratory evaluation in SCD patients suggests that microorganisms are involved in the modulation of chronic inflammatory. The association of colonized microorganisms and laboratorial markers suggest a new approach to these patients follow-up, and additional studies of microorganism colonisation and their association with SCD patients’ clinical outcome will improve control and prevention strategies.